DESIGNING PORTAL AMAZING NORTH SULAWESI AS PART OF INDONESIAN E-CULTURAL HERITAGE AND NATURAL HISTORY - Stanley Karouw; Hans Wowor (Jurnal Sistem Informasi, 2013)
Digital preservation is one of the ways to make tourism of a nation keeps alive. The tourism of a nation rooted in its culture and nature. The wealth of these tourism spread in many entitites and areas such as cultures and natures. ICT role as key enabler to preserve this cultures and nature tourism. In this paper we proposed a Web Portal following eCultural Heritage and Natural History (eCHNH) Framework. This portal is to increase accessibility, provide availability and comply multi-content for culture and nature tourism of North Sulawesi. We used Agile Unified Process (AUP) Methodology to develop this web portal to emphasize user-oriented and object-oriented development paradigm. This agile-characteristic would produce web-based applications that meet user expectations and needs.